2014
DOI: 10.3109/09638288.2014.972588
|View full text |Cite
|
Sign up to set email alerts
|

Activity engagement and health quality of life in people with Parkinson’s disease

Abstract: This study provides preliminary evidence that regular participation in community programs like BPg may increase retention rates of activity engagement in people with PD. Participation in BPg programs, though, was not shown to improve HQoL as measured by the PDQ-39. Implications for Rehabilitation Continued participation in a wide repertoire of activities is a valuable rehabilitation goal for clients with Parkinson's disease (PD). People with PD who participate in specially designed community-based programs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Quality of life (QOL) also plays an important role in independent living. For instance, happier people are more active in their daily lives and maintain better physical health 9 ) . Therefore, maintaining high QOL could be a key factor during the rehabilitation of people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life (QOL) also plays an important role in independent living. For instance, happier people are more active in their daily lives and maintain better physical health 9 ) . Therefore, maintaining high QOL could be a key factor during the rehabilitation of people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of participation in activities (mainly domestic) improved among a single (noncontrolled) group of people 50 years and over attending a creative dance program once a week for 6 weeks (O'Toole et al, 2015). Sabari et al (2015) reported people with Parkinson's disease participating in a community-based dance group for at least 6 months (at least once a week) being significantly more engaged in social activities compared to a nonparticipating group. In a randomized control trial, Foster et al (2013) demonstrated that an intervention of 1 h, 2 times a week for 12 months of tango dance significantly improved participation in complex activities of daily living, in the recovery of activities lost since diagnosis and engagement in new activities compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a qualitative study found that some participants among a group of elderly women reported that since they had been part of the dance group, they were no longer afraid of what others thought of them (Nadasen, 2008). Other participants expressed their great satisfaction with their dance group/intervention, reporting, for example, that they feel inspired and focused on what they can do doing their dance group (Sabari et al, 2015). These comments are consistent with the significant improvement demonstrated in our study in the dimensions of "sense of control" and "loss of selfconsciousness."…”
Section: Discussionmentioning
confidence: 99%
“…As far as the researchers are aware, this has not been previously identified as a component of wellbeing for people with PD. Most of the literature related to wellbeing and PD has focused on maintaining function, receiving appropriate support and maintaining social relationships (see, for example, Behari et al., 2005; Duncan and Earhart, 2011; Forsaa et al., 2008; Müller et al., 2013; Sabari et al., 2015), and none of the standardised measures used in these studies explicitly listed being able to contribute as an item that was measured.…”
Section: Discussionmentioning
confidence: 99%